Social Work in Addictions and Health Care - NEAMȚU, Nicoleta; ȘTEFANI, Sebastian Claudiu (2023)
This volume includes a selection of papers presented at the thirteenthedition of the international conference: "Social Work in the Addictions andHealth Care – Interdisciplinary Collaboration to Improve Quality of Servicesand Quality of Life", which took place in Alba Iulia during December 9-10.The conference organized by the ”1 Decembrie 1918” University ofAlba Iulia aimed to bring together researchers and practitioners in the fieldof social work applied in the field of health and addictions to share theresults of research and professional practice.